Near Infrared Light Sensitive Ultraviolet–Blue Nanophotoswitch for Imaging-Guided “Off–On” Therapy - Zuo, Jing; Tu, Langping; Li, Qiqing; Feng, Yansong; Que, Ivo; Zhang, Youlin; Liu, Xiaomin; Xue, Bin; Cruz, Luis J; Chang, Yulei; Zhang, Hong; Kong, Xianggui (ACS nano, 2018)
Photoswitchable materials are important in broad applications. Recently appeared inorganic photoswitchable upconversion nanoparticles (PUCNPs) become a competitive candidate to surmount the widespread issue of the organic counterparts photobleaching. However, current PUCNPs follow solely Yb3+/Nd3+ cosensitizing mode, which results in complex multilayer doping patterns and imperfectness of switching in UV–blue region. In this work, we have adopted a new strategy to construct Nd3+ free PUCNPsNaErF4@NaYF4@NaYbF4:0.5%Tm@NaYF4. These PUCNPs demonstrate the superior property of photoswitching. A prominent UV–blue emission from Tm3+ is turned on upon 980 nm excitation, which can be completely turned off by 800 nm light. The quasi-monochromatic red upconversion emission upon 800 nm excitationa distinct feature of undoping NaErF4 upconversion systemendows the PUCNPs with promising image-guided photoinduced “off–on” therapy in biomedicine. As a proof-of-concept we have demonstrated the imaging-guided photodynamic therapy (PDT) of cancer, where 800 nm excitation turns off the UV–blue emission and leaves the emission at 660 nm for imaging. Once the tumor site is targeted, excitation switching to 980 nm results in UV–blue emission and the red emission. The former is used to induce PDT, whereas the latter is to monitor the therapeutic process. Our study implies that this upconversion photoswitching material is suitable for real-time imaging and image-guided therapy under temporal and spatial control.